Sistem Pendukung Keputusan Penerima Bantuan Bibit Bawang Merah Di Kecamatan Karang Dapo - Hamidani, Syafiul; Apriadi, Deni (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
The growth of the agricultural sector, especially in shallot production, has become the main focus in supporting food security in Musi Rawas Utara Regency which has been faced with the challenge of how to create smarter and more focused agricultural strategies. The agriculture and fisheries department has so far used a computerized system but not yet. decision support system, one of which is the distribution of seed aid to farmers to increase production yields, so it is felt that there is a need to develop and implement a decision support system for recipients of shallot seed aid because shallots are one of the mainstay commodities focused on by the Musi Rawas Utara Agriculture and Fisheries Service in Karang Dapo sub-district, this research uses the weighted product method which uses 6 criteria, namely harvest scale, land area, number of members of the farmer group, requirements for prospective locations and requirements for prospective farmer groups whose requirements have been determined by the agriculture and fisheries service which resulted in the Danau Gede farmer group being The preference with the largest value from the other 11 alternatives is with a vector value V = 0.07978270931306.